Surgical Management of Tibialis Anterior Tendon Ruptures: A Systematic Review and Proposed Treatment Algorithm. Issue 4 (November 2022) - Weiss, Matthew B.; Azam, Mohammad T.; Ubillus, Hugo A.; Gianakos, Arianna L.; Kirschner, Noah; Walls, Raymond J.; Kennedy, John G.
Category: Sports; Other Introduction/Purpose: Although rare, Tibialis Anterior Tendon (TAT) tears or ruptures can have a detrimental effect on patients' quality of life. There is no current consensus as to the most appropriate surgical treatment for TAT rupture, in part because of the paucity of data surrounding this condition. Therefore, this study attempts to address this deficiency by performing a systematic review of the literature of the different surgical interventions for TAT rupture, analyzing the level of evidence (LoE) and quality of evidence (QoE) of the included studies, and recommending an algorithm approach to the surgical treatment of TAT injury. Methods: In September 2021, the MEDLINE and EMBASE databases were systematically reviewed based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The following search terms were used: (anterior) AND (tibialis OR tibial) AND (tendon) AND (tear OR rupture) NOT (acl OR cruciate OR meniscal OR patellar). ??Full-length peer-reviewed studies in English with a sample size of 5 participants that reported functional outcome scores were included. We excluded systematic reviews, meta-analyses, review articles, and case series/reports with less than five participants. The LoE and QoE of the included studies were evaluated using the Journal of Bone and Joint Surgery Criteria and the Modified Coleman Methodology Score, respectively. In some cases, tabulated data from studies were analyzed to obtain relevant statistics for our analysis, including deriving descriptive statistics such as mean and standard deviation values, as well calculating p-values with two- sample t-tests assuming either equal or unequal variance. Results: Twelve studies with 171 patients were included in this review, 11 with Level IV evidence and one with Level II evidence. Additionally, there were 17 different types of repair techniques used, where direct repair (including end-to-end repair and bone fixation) was performed on 33.5% of tendons, tendon transfers were performed on 20.8% of tendons, and grafts were performed on 45.7% of tendons. For the mean postoperative AOFAS Ankle-Hindfoot (AOFAS-AH) scores, both the direct repair and autograft cohorts had significantly higher mean scores than the allograft cohort (p=0.008 and p=0.002 respectively). The autograft cohort was also found to have significantly higher post-operative means AOFAS-AH than the tendon transfer cohort (p=0.047). We also found statistically significant improvements in dorsiflexion strength after surgical intervention in early intervention (<=6 weeks from injury to surgery) and delayed intervention cohorts. Conclusion: Surgical management of TAT ruptures produces good clinical outcomes in the intermediate follow-up. As there is no current consensus on the most appropriate surgical treatment, we have designed a treatment algorithm based upon the current literature citing statistical evidence determined in this systematic review.